Crime and the planning of residential areas- a comparative analysis of two Taman Melati terrace housing units - Elsawahli, Hanan Mohamed Hassan; Mohit, Mohammad Abdul (2010)
Globally, the design of the built environment has played a crucial role in preventing design. Increasingly, two school of thoughts namely Defensible Space and New Urbanism are seen as guiding the CPTED agenda for the coming decades. This paper aims to explore the relationship between residential crime and the design of the built environment in relation to these design concepts. The study analyses and compares the safety level in Taman Melati Terrace Housing in two different locations, which have characteristics of Defensible Space and New Urbanism. Although there are many studies examining the relationship between the design of the built environment and crime occurrence, only few examined the built environment design as complying with the two concepts design principles. There is little research in Malaysia supporting this argument or rejecting it. This paper aims to examine the form of the built environment (Defensible Space/New Urbanism) that has an impact on the safety level. The results showed that the housing location complying with New Urbanism planning principles had a higher safety level than the housing location complying with Defensible Space planning principles.